A Rare Intraoral Manifestation of Nevus of Ota - A Case Report - Nair, Mithula; Castelino, Renita L; Ajila, Vidya; Babu, Subhas G; Ghosh, Rumela (UI Scholars Hub, 2016)
Nevus of Ota is a dermal melanocytic nevus which is characterized by benign hamartomatous hyperpigmentation. Clinically it presents as a congenital or acquired blue or gray patch on the face and is distributed on the ophthalmic, maxillary, and mandibular branches of the trigeminal nerve. It is most commonly found in Japanese populations and is rare in the Indian subcontinent. It affects only 0.014 – 0.034% of the Asian population and is less common in the male population, with a male to female ratio of 1.4:8. The involvement of pigmentation over the pinna of the ear and the oral mucosa is extremely rare with very few cases reported in scientific literature. The case reported here is a case of nevus of Ota, with a rare intraoral presentation on the hard palate, crossing the midline.